Creating Structure in a Time of Intense Stress: Treating Intimate Partner Violence. Issue 2 (3rd April 2019) - Rouleau, Erica; Barabe, Teresa; Blow, Adrian
Abstract: Violence is an increasingly visible problem in the United States, with the news and other forms of media bringing this into the forefront of the public's awareness. Violence comes in many different forms, including intimate partner violence (IPV), which occurs for about 36% of women and about 29% of men across the United States. Given the high incidence in the United States, it is imperative to consider the best ways for mental health professionals to treat violence in relationships. Some professionals in the field have developed and utilized conjoint treatment models for working with couples who have a history of violence. This article presents the application of attachment theory to a conjoint treatment model for couples that have experienced violence. A case study is included to demonstrate the implementation of an emotionally focused therapy framework and provide a sample outcome of this treatment approach. The framework of this article provides clinicians with insight into how to approach working with violent couples in a safe and productive way. Mental health professionals are at the front lines of implementing evidence-based interventions and creating lasting change for the clients whom they work with.